(untitled) (Research, Society and Development, 2022)
The objective was to investigate dietary and oral hygiene patterns as risk factors for dental caries, fluorosis and tooth erosion in a subsample of individuals of a population-based study in the city of João Pessoa (without water fluoridation program), Brazil. In this cross-sectional study data were collected through clinical examinations and questionnaires addressing dietary and oral hygiene habits. The clinical examination was performed by two calibrated examiners (Kappa > 0.80). The sample (n = 244) was distributed among four age groups: G1 (0-13 years), G2 (14-30 years), G3 (31-54 years) and G4 (≥ 55 years). The prevalence of dental caries was high (87.4%) whereas fluorosis and erosion was low (4.1% and 6.1%, respectively). The mean DMFT index was 1.49 ± 2.19 in G1, 8.19 ± 6.10 in G2, 18.19 ± 7.00 in G3 and 25.81 ± 6.80 in G4. Significant associations were found between the DMFT index and both diet (p = 0.05) and income (p = 0.022), suggesting an associated effect of these variables. Oral hygiene was not related to dental caries experience. Cariogenic diet was related to the high DMFT index in all age groups supporting that dietary pattern was a stronger risk factor for caries experience in contrast to oral hygiene habits that no association was found.